2012
DOI: 10.1371/journal.pone.0029150
|View full text |Cite
|
Sign up to set email alerts
|

Wolfram Syndrome: New Mutations, Different Phenotype

Abstract: BackgroundWolfram Syndrome (WS) is an autosomal recessive neurodegenerative disorder characterized by Diabetes Insipidus, Diabetes Mellitus, Optic Atrophy, and Deafness identified by the acronym “DIDMOAD”. The WS gene, WFS1, encodes a transmembrane protein called Wolframin, which recent evidence suggests may serve as a novel endoplasmic reticulum calcium channel in pancreatic β-cells and neurons. WS is a rare disease, with an estimated prevalence of 1/550.000 children, with a carrier frequency of 1/354.The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 43 publications
(50 reference statements)
4
46
1
3
Order By: Relevance
“…36 We analyzed as mutations (i) c.2020G→A (p.Gly674Arg), considered either a mutation 37 or a polymorphism, 38 and (ii) c.1367G→A (p.Arg456His), considered either a mutation 34 or a polymorphism, [31][32][33]39,40 because both are predicted to produce deleterious proteins by Condel 41 and PolyPhen-2. 42 c.2020G→A is also considered a mutation in the LOVD-WFS1 database.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 We analyzed as mutations (i) c.2020G→A (p.Gly674Arg), considered either a mutation 37 or a polymorphism, 38 and (ii) c.1367G→A (p.Arg456His), considered either a mutation 34 or a polymorphism, [31][32][33]39,40 because both are predicted to produce deleterious proteins by Condel 41 and PolyPhen-2. 42 c.2020G→A is also considered a mutation in the LOVD-WFS1 database.…”
Section: Patientsmentioning
confidence: 99%
“…We considered as polymorphisms c.*47C→T 33,43,44 and c.*253G→A 37 because they locate to the 3′-untranslated region of WFS1 mRNA, and c.316-37C→T because its effects on splicing have not been indicated. 34 Supplementary Table S2 online lists all the mutations described in the patients.…”
Section: Patientsmentioning
confidence: 99%
“…Aloi et al, reported a Wolfram syndrome patient with surgically repaired tetralogy of Fallot due to a compound heterozygous mutation, c.1628T>G and c.2104G>A. 7 In the series by Strom et al, the patient harboring the mutation, as our patient, (c.1523delAT) exhibited a severe phenotype with an early onset of cardinal clinical manifestations including abnormal EEG and retarded sexual maturation. In the reported case, the finding of a WFS1 mutation in exon 8 was not associated with a cardiac anomaly.…”
Section: Discussionmentioning
confidence: 53%
“…Wolframin has a role in maintaining the homeostasis of endoplasmic reticulum in pancreatic β cells. 3 Cardiac malformations in Wolfram syndrome have been reported rarely [4][5][6][7] and may be responsible for the morbidity and mortality of the disorder. We present a case with Wolfram syndrome accompanied by tetralogy of Fallot and discuss the findings with reference to literature.…”
Section: Association Of Wolfram Syndrome With Fallot Tetralogy In a Girlmentioning
confidence: 99%
“…Aloi y col., informaron sobre un paciente con síndrome de Wolfram con tetralogía de Fallot sometida a reparación quirúrgica debido a una mutación heterocigota compuesta, c.1628T>G y c.2104G>A. 7 En una serie de Strom y col., el paciente que tenía la mutación (c.1523delAT), como nuestra paciente, tenía un fenotipo grave con la aparición temprana de manifestaciones clínicas primordiales, entre otras, anomalías en el EEG y retraso de la madurez sexual. En el caso notificado, el hallazgo de una mutación en el exón 8 del gen WFS1 no estaba asociado con anomalía cardíaca.…”
Section: I V E R S a S A L T E R A C I O N E S G E N é T I C A S S unclassified